Exploring the Mechanisms Underlying the Effectiveness of Psychosocial Aftercare in Pediatric Chronic Pain Treatment: A Qualitative Approach - Meltem Dogan; Almut Hartenstein-Pinter; Susanne Lopez Lumbi; Markus Blankenburg; Michael C. Frühwald; Rosemarie Ahnert; Sarah Braun; Ursula Marschall; Boris Zernikow; Julia Wager (MDPI AG, 2022)
A newly developed specialized psychosocial aftercare program (PAC) for pediatric patients with chronic pain following an intensive interdisciplinary pain treatment (IIPT) was found to be significantly more effective than IIPT alone. This qualitative study aimed to gain further insight into the mechanisms and prerequisites for the effectiveness of this specialized aftercare program. We conducted structured telephone interviews with patients, parents, and health care professionals conducting PAC. A total of 16 interviews were conducted-seven interviews with parents, six interviews with patients, and three interviews with health care professionals-and transcribed verbatim. Data were analyzed using reflexive thematic analysis. Four major themes consisting of 20 subcategories were identified, namely (1) frame conditions, (2) person factors, (3) stabilization and (4) catalyst. The foundations of treatment success are frame conditions, such as flexibility or constancy, and person factors, such as respect or expertise. Based on these foundations, stabilization is achieved through security, mediation, orientation and support. Altogether, these components of PAC reveal their potential as catalysts for further improvement even after discharge from IIPT. Overall, patients and their families emphasized widespread personal relevance and acceptance of the PAC program. The findings of this study may be employed in the development of other aftercare programs or interventions involving families in the context of psychotherapeutic and psychosocial health care.